The Edu-Innovation of Smoke Level Waste Incidents and Composters from Reused Gallons in Kalibaros Village - Mansur Chadi Mursid; Dewi Halimatus Sarah; Haidhar Ali Zulfikar; Risxi Nizar Afandi; Alya Safira Husna; Annisa Arifiyah; Sintha Anggraeni; Malahayati Ulimas; Alya Rachma; Yonanda Dwi Hansya; Zuhrotul Fu'adah; Naufal Dermawan; Daryl M. De Asis (GUYUB: Journal of Community Engagement, 2025)
The rubbish problem in Indonesia, especially in densely populated areas such as Kalibaros Village, Pekalongan City, is increasingly severe and negatively impacts the environment. This study aims to educate the community about the separation of organic and inorganic rubbish and introduce an innovative low-smoke rubbish incineration device and the production of compost from used gallons. The method used in this community service is Participatory Action Research (PAR). The results showed an increase in community awareness, 95% of participants reported an increased understanding of waste sorting after the training. The innovative low-smoke incineration device successfully reduced air pollution emissions, while the composting of organic rubbish provided dual benefits by reducing rubbish and producing natural fertilizer. This activity is expected to continue with regular assistance to ensure the sustainability of rubbish separation and management practices in the community.